2017
DOI: 10.1017/s0007485316001012
|View full text |Cite
|
Sign up to set email alerts
|

Long-chain alkanes and fatty acids fromLudwigia octovalvisweed leaf surface waxes as short-range attractant and ovipositional stimulant toAltica cyanea(Weber) (Coleoptera: Chrysomelidae)

Abstract: The importance of leaf surface wax compounds from the rice-field weed Ludwigia octovalvis (Jacq.) Raven (Onagraceae) was determined in the flea beetle Altica cyanea (Weber) (Coleoptera: Chrysomelidae). Extraction, thin layer chromatography and GC-MS and GC-FID analyses of surface waxes of young, mature and senescent leaves revealed 20, 19 and 19 n-alkanes between n-C15 and n-C35, respectively; whereas 14, 14 and 12 free fatty acids between C12:0 and C22:0 fatty acids were identified in young, mature and senesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…Some insects can use the plant wax metabolites, and specifically the alkanes, as oviposition stimulants (e.g. Spencer 1996 , Müller and Hilker 2001 , Mitra et al 2017 ). The reasons why thrips or other insects prefer plants with more alkanes are thus far unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some insects can use the plant wax metabolites, and specifically the alkanes, as oviposition stimulants (e.g. Spencer 1996 , Müller and Hilker 2001 , Mitra et al 2017 ). The reasons why thrips or other insects prefer plants with more alkanes are thus far unknown.…”
Section: Discussionmentioning
confidence: 99%
“…For example, amyrins (triterpenoids) reduced feeding by diamandback moth larvae on cabbage (Eigenbrode and Pillai 1998 ). On the other hand, some wax metabolites can also be used for host plant recognition and as feeding stimulants by various insects such as sawflies and flea beetles (Braccini et al 2015 ; Mitra et al 2017 ; Müller and Hilker 2001 ; Udayagiri and Mason 1997 ). Relatively high amounts of leaf wax have been associated with higher susceptibility against thrips in onions and leak (Damon et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of very low amounts of compounds at the high end of the homolog distribution suggested that they are formed merely as by-products of the normal wax biosynthesis machinery rather than through dedicated processes specific to their chain lengths. Characterization of enzymes involved in wax precursor elongation in respective species may reveal whether, in these cases, single FAEs indeed form both the ubiquitous chain lengths and the C 35+ homologs [ 2 , 6 , 23 , 39 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ].…”
Section: Extra-long Compounds In the Wax Mixtures Of Diverse Plantmentioning
confidence: 99%
“…Data were normally distributed as determined by Shapiro-Wilk tests (except those individual compounds which are not present in all treatments), and so data were analysed with one-way ANOVA followed by Tukey's test (Zar, 1999). Data on behavioural responses of A. cyanea to VOCs were analysed by v 2 test (H 0 : P = 50%) (Adhikary et al, 2015;Mitra et al, 2017b). Insects that remained in the stem of the olfactometer were excluded from the analyses.…”
Section: Discussionmentioning
confidence: 99%